Stakeholders Perspectives on the Introduction of an Additional Injectable Vaccine Under the Universal Immunization Programme in India - Pawan Kumar; Rashmi Mehra; Arindam Ray; Amrita Kumari; Kapil Singh; Rhythm Hora; Amanjot Kaur; Seema S. Koshal; Syed F. Quadri; Shyam Kumar Singh; Abida Sultana; Arup Deb Roy (Vaccines)
Introduction: In 2023, India’s National Technical Advisory Group on Immunization (NTAGI) recommended the inclusion of typhoid conjugate vaccine (TCV) in the Universal Immunization Programme (UIP). However, introducing TCV, an additional injectable vaccine (AIV), will potentially increase the number of injections administered in a single visit to a maximum of five (if given at the 9 to 12 months touchpoint) or four (if given in the second year of life). In this context, the present study aimed to explore the perspectives of program managers, service providers, and caregivers regarding introduction of an AIV in a single visit under the UIP. Methods: A mixed-method study was undertaken wherein quantitative data was collected by telephonic surveys, and qualitative data by key informant interviews (KIIs) and focus group discussions (FGDs). Purposive sampling encompassed eight states, eight districts, eight planning units, and 32 session sites. The qualitative data were thematically analyzed manually using Excel, while the quantitative data was analyzed using STATA 17. Results: A total of 1140 telephonic surveys, 96 KIIs, and 16 FGDs were conducted. The study revealed that program managers mentioned maternal emotional reactions as a significant concern and backed AIV introduction at the 9–12 months touchpoint. Vaccinators and community mobilizers favored the 16–24 months window with combined presentations and mentioned single-dose vials as the preferred approach for vaccine delivery. Caregivers acknowledged the benefits of vaccination but expressed discomfort and fear regarding multiple injections to the child in a single visit. Caregivers expressed a preference for a combination vaccine. No preference was reported among caregivers for the introduction of AIV to the 9–12 or 16–24 months touchpoints. Conclusion: Stakeholders’ perspectives on introducing an additional injectable vaccine in a single visit under the UIP are diverse. These will be helpful in developing an effective strategy for the future introduction of AIV under UIP.